Race-based trauma and post-traumatic growth through identity transformation - Chin, Dorothy; Smith-Clapham, Amber M.; Wyatt, Gail E. (Frontiers in Psychology, 2023)
Race-based trauma has been linked to multiple negative health and mental health outcomes, including hypertension, post-traumatic stress, anxiety, and depression. While the possibility of post-traumatic growth (PTG) has been investigated following other types of trauma, relatively less work has been done on PTG following race-based trauma. This conceptual analysis examines the relationship between race-based trauma and PTG, in particular the role of racial identity narratives. Based on the work of Claire Jean Kim (1999) on Black and Asian American identity and integrating theory and research on historical trauma and PTG, we present a framework in which the transformation of externally imposed narratives into more authentic, internally generated ones serves as a catalyst that sparks post-traumatic growth after racial trauma. Based on this framework, mechanisms that enact the cognitive processes of PTG are offered, including storytelling, writing, visual art and other media, as well as suggestions for their practical implementation.